Produção de biodiesel: desenvolvimento de metodologias alternativas de quantificação e síntese de catalisadores a base de óxido de zinco - Fabiana Pereira de Sousa (2011)
The most commonly used catalysts for the synthesis of biodiesel are the homogeneous alkaline catalysts, due to faster reaction and which give higher yields, not requiring high pressures, temperatures and molar ratios alcohol: oil. However this type of catalysis requires washing steps for the purification of biodiesel in order to remove residual catalyst. This wash on an industrial scale, it generates a large amount of effluent that must be treated before being discarded, leaving the costly process. In this context, heterogeneous catalysis has gained great prominence for the synthesis of biodiesel. In this study, were synthesized, characterized and tested ZnO based catalysts for synthesis of biodiesel. Among thecatalysts tested, the Ba / commercial ZnO showed the best efficiency, withconversions above 96%, the molar ratio of oil: ethanol 1:12, for 2 hours under reflux and magnetic stirring. In parallel, form developed analytical techniques for the quantification of alkyl esters, and the viscometry was highlighted because it was efficient, with errors of around 3% compared to CG, and because it is an inexpensive and portable method